Attributions of survival and methods of coping of long-term ovarian cancer survivors: a qualitative study - Dana Ketcher; Susan K. Lutgendorf; Susan Leighton; Marianne Matzo; Jeanne Carter; Arjun Peddireddy; Beth Y. Karlan; William P. Tew; Anil K. Sood; Eileen H. Shinn (BMC, 2021)
Abstract Background Only 8-23% of advanced epithelial ovarian cancer patients survive for 10 years or longer. Given the need for targeted interventions to improve survival, we interviewed this relatively rare survivor population to gain personalized insights into the reasons for their survival. The aim of this study was to characterize subjective attributions of survival and specific coping mechanisms long-term survivors of ovarian cancer. Methods Twenty-two semi-structured, qualitative interviews assessing survival attributions and coping strategies were conducted from April to November 2014. Data were analyzed in a multistep process using ATLAS.ti.8: codes were identified during review of the transcripts and refined with literature review; the frequency of codes and code co-occurrence was calculated, and codes were grouped into themes. Resulting themes were checked by a national leader of an ovarian cancer advocacy organization and compared against available literature. Results Thematic analysis found that participants credited their long-term survival to a variety of factors including medical, social, religious/spiritual, and lifestyle/personal characteristics. Some participants rejected these same attributions, concluding that the reason for survival was due to luck or unknowable. Several of Carver et al.'s theoretical dimensions of coping were evident in our sample: planning, positive reinterpretation, social support, religion and acceptance whereas three relatively new strategies were uncovered: conserving emotional energy, value-based activity coping, and self-care. Conclusions Long-term survivors' perspectives were largely consistent with those of newly diagnosed ovarian cancer patients and ovarian cancer survivors of shorter duration. However, the long-term survivors were also willing to reject conventional attributions for survival and recognized the importance of disciplined self-preservational coping strategies.